The Super Spreadsheet: collaborative information infrastructure in translational teams - Venkatesh, Shruthi; Rolland, Betsy (Frontiers in Psychology, 2026)
IntroductionScience teams rely on multiple types of information to communicate, coordinate, and collaborate on their research and operational endeavors. While the Science of Team Science (SciTS) offers robust literature on how such teams use and manage their data, we know relatively little about their collective information behaviors. This paper, the first in a series, reports findings from the Information Management Prototype for Clinical and Translational Research (IMPACT-CTR) study, which examines collaborative information infrastructure within one type of science team: clinical and translational research teams (CTRTs).MethodsWe interviewed 48 team members across 10 U.S.-based teams.ResultsAnalyses revealed that CTRTs progress through the research lifecycle of their collaborations by maneuvering several types of information dispersed across various tools, while simultaneously managing their individual information organizational styles in relation to those of their team members. Unlike data, the role of information in their work was often overlooked or undervalued. Teams with misaligned information management experienced time lags and slower project progress, whereas alignment fostered fluency in their work.DiscussionBy generating a typology of information and identifying tensions between individual and collective information practices, this study facilitates our understanding of how to support rigorous and reproducible team science practices in CTRTs.